A titanium-based perovskite oxide heterojunction catalytic material and its preparation method and application

By constructing the Z-type heterojunction of MgxTiyO5 and In2S3, the problem of insufficient purity and light absorption in the preparation of titanium-based perovskite oxide materials is solved, and high-efficiency photocatalytic activity and stability are achieved, which can effectively degrade pollutants and have simple Preparation process and good reusability.

CN118698563BActive Publication Date: 2025-01-17中国市政工程西北设计研究院有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411202345.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-17
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The existing titanium-based perovskite oxide materials have complex preparation processes, which are prone to affect the purity of the accompanying products. The electron-hole recombination rate of a single material is high and the visible light absorption is insufficient, resulting in low photocatalytic activity.

Method used

By constructing the Z-type heterojunction of MgxTiyO5 and In2S3, the energy band structure of the material is adjusted, and the narrow band gap and high chemical stability of In2S3 are used to enhance the light absorption and interface charge separation efficiency and reduce the electron-hole recombination rate.

Benefits of technology

It realizes efficient visible light absorption of the material, improves photocatalytic activity and stability, can efficiently degrade pollutants, and has a simple preparation process and good reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118698563B_ABST
    Figure CN118698563B_ABST
Patent Text Reader

Abstract

The present invention discloses a titanium-based perovskite oxide heterojunction catalytic material and its preparation method and application, which belongs to the field of photocatalysts. The preparation method of the present invention comprises dissolving magnesium nitrate hexahydrate and urea in deionized water, then dispersing titanium isopropoxide in ethylene glycol solution, mixing the above two solutions; then continuously stirring the solution mixture under heating conditions until the solvent is completely evaporated; finally, calcining the obtained powder to remove impurity ions, and obtaining nanoparticles of Mg x Ti y O5; Mg x Ti y O5, InCl3·4H2O, thioacetamide and urea were dispersed in an ethanol aqueous solution. After continuous stirring, the solution was subjected to a hydrothermal reaction. After the solution was naturally cooled to room temperature, it was centrifuged, washed, and then dried to a constant weight to obtain a catalytic material Mg x Ti y O5 / In2S3. This photocatalytic system achieves effective pollutant degradation and has the characteristics of simple synthesis method, good stability and reusability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photocatalysts, and in particular relates to a titanium-based perovskite oxide heterojunction catalytic material and a preparation method and application thereof. Background Art

[0002] The construction of heterojunction has been proven to be one of the most promising methods in the field of photocatalysis, which can suppress the recombination rate of photogenerated electrons, expand the visible light absorption range, improve the photocatalytic activity, and realize the advantages of these two materials. x Ti y Magnesium titanates of O5 have unique layered and perovskite or tunnel-like crystal structures and are gaining increasing attention due to their negative conduction band position and high photocatalytic activity. The theoretical band gap energy of MgTi2O5 is about 3.4 eV, and it contains Ti 4+ d 0 Metal ions (metal ions without electrons in the d orbital) have potential catalytic activity. However, the preparation process of pure orthorhombic MgTi2O5 materials is difficult because other magnesium titanate byproducts, such as MgTiO3, may appear during the preparation process, and the appearance of byproducts will affect the overall purity of the material. In addition, the high electron-hole recombination rate and insufficient visible light absorption of a single material also affect its photocatalytic activity.

[0003] Magnesium titanate (Mg x Ti y MgTi2O5) is a titanium-based perovskite oxide with a unique layered and perovskite or tunnel-like crystal structure, and is considered to be an important indirect wide bandgap semiconductor. The theoretical bandgap energy of MgTi2O5 is about 3.4 eV, and it contains Ti 4+ , d 0 Metal ions have potential catalytic activity. MgTi2O5 has a negative conduction band, high chemical stability and photocatalytic activity. As an ultraviolet (UV) responsive photocatalyst, its band structure can be adjusted by changing the ratio of magnesium to titanium, so it has great development potential in the field of photocatalysis. However, the preparation process of pure orthorhombic MgTi2O5 material is difficult. This is because other magnesium titanate by-products, such as MgTiO3, may appear during the preparation process. The appearance of by-products will affect the overall purity of the material. In addition, the high electron-hole recombination rate and insufficient visible light absorption of a single material also affect its photocatalytic activity. x Ti y Coupling O5 with semiconductors with matching band gaps to construct heterojunctions is an effective strategy to promote charge separation and improve light absorption, thereby enhancing photocatalytic performance.

[0004] People usually use other semiconductors such as g-C3N4, CdSe and MgTi2O5 to enhance charge separation and extend the electron lifetime, thereby reducing energy loss during the reaction. However, the light absorption cutoff edge of single g-C3N4 is about 450nm, and the light absorption cutoff edge of CdSe is about 550nm, which means that such composite materials cannot effectively utilize visible light of 550nm-800nm. In short, even if the composite heterojunction is constructed, the catalytic efficiency is reduced due to insufficient visible light absorption. Compared with g-C3N4 and CdSe, In2S3 has attracted much attention due to its narrow bandgap (1.5-2.1 eV), stability and morphological adjustability. In2S3 has excellent chemical stability and good thermal stability, making it very suitable for photocatalytic applications. Its ultra-thin structure makes it easy for electrons and holes to transfer from the inside to the surface, while its solid specific surface area enhances the adsorption and desorption of reactants and products. In addition, its narrow band gap of only 2.0 ~ 2.3 eV ensures effective absorption of visible light. In addition, the negative conduction band (CB) potential provides a strong reducing ability, satisfying the thermodynamic prerequisite for the oxidation of water molecules and dissolved oxygen into reactive oxygen species. However, the widespread use of In2S3 as a photocatalyst faces challenges due to its high electron-hole recombination rate and low valence band position, which limit its oxidation ability.

[0005] The light absorption cutoff edge of In2S3 is about 650nm, and it also has a certain absorption tail peak, which means that the compounding of MgTi2O5 and In2S3 can make it absorb more visible light. In addition to the complementary visible light absorption, another factor to consider in constructing heterojunctions is the relative position of the material energy bands. x Ti y The energy band structure of O5 can be adjusted by changing the ratio of magnesium / titanium. Usually, the valence band position of MgTi2O5 is about 3.1eV, and the conduction band position is about -0.3eV, while the valence band position of In2S3 is about 1.2eV, and the conduction band position is about -0.9eV. The matching energy level structure means that when the two form a heterojunction, photogenerated electrons can be transferred from MgTi2O5 to the In2S3 surface, thereby suppressing the in situ recombination of electron-hole pairs. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a titanium-based perovskite oxide heterojunction catalytic material, so as to develop a titanium-based perovskite oxide heterojunction catalytic material with simple preparation process, higher material purity, stronger visible light absorption, higher interface charge separation efficiency, better stability, reusability, and the ability to achieve photocatalytic degradation of organic pollutants.

[0007] Another object of the present invention is to provide a titanium-based perovskite oxide heterojunction catalytic material.

[0008] The third object of the present invention is to provide an application of a titanium-based perovskite oxide heterojunction catalytic material.

[0009] The technical solution of the present invention is: (one)

[0011] A method for preparing a titanium-based perovskite oxide heterojunction catalytic material comprises the following steps:

[0012] A. A certain amount of magnesium nitrate hexahydrate and urea are dissolved in deionized water, and then a certain amount of titanium isopropoxide is dispersed in ethylene glycol solution, and the above two solutions are placed in a round-bottom flask for mixing; then the solution mixture is continuously stirred under heating conditions until the solvent is completely evaporated; finally, the obtained white powder is placed in a muffle furnace for calcination to remove impurity ions, and nanoparticles of Mg x Ti y O5;

[0013] B. Add a certain molar ratio of Mg x Ti y O5, InCl3·4H2O, thioacetamide and urea were dispersed in an ethanol aqueous solution. After continuous stirring at 600 r / min for 60 min, the solution was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction. After the solution was naturally cooled to room temperature, it was centrifuged, washed with deionized water and ethanol three times each, and then dried at 60 °C to constant weight to obtain a yellow catalytic material Mg x Ti y O5 / In2S3.

[0014] As a further improvement of the present invention, in step A, the mass ratio of magnesium nitrate hexahydrate, urea and titanium isopropoxide is 3-4:12:5-6.

[0015] As a further improvement of the present invention, in step A, the solution mixture is heated to 80-100°C.

[0016] As a further improvement of the present invention, in step A, the calcination temperature is increased to 500-600° C. at a rate of 2-10° C. / min and the calcination is performed for 2-4 hours.

[0017] As a further improvement of the present invention, in step B, Mg x Ti y The molar ratio of O5, InCl3·4H2O, thioacetamide and urea is 0.25-1.0:1:2:1.7.

[0018] As a further improvement of the present invention, in step B, the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 10-14 h.

[0019] The present invention combines magnesium titanate material and indium sulfide material. The full visible spectrum absorption and the presence of heterojunction effectively improve the light capture and interface separation efficiency, so that the titanium-based perovskite oxide heterojunction material can efficiently degrade pollutants under the action of ultraviolet and visible light, and has the characteristics of good stability in the aqueous phase and recyclability. (two)

[0021] A titanium-based perovskite oxide heterojunction catalytic material is prepared by the preparation method of the titanium-based perovskite oxide heterojunction catalytic material. (three)

[0023] A titanium-based perovskite oxide heterojunction catalytic material is used in the photocatalytic degradation of pollutants.

[0024] Further, the contaminants include bisphenol A.

[0025] Indium sulfide (In2S3) has the same x Ti y O5 has a matching energy level structure, and the matching valence band and conduction band positions enable the two to form a heterojunction structure. The present invention synthesizes a Mg x Ti y O5 / In2S3 Z-type heterojunction, photodegradation of pollutant bisphenol A under UV and visible light irradiation. Mg x Ti y The wide band gap of O5 means that when the material is excited by ultraviolet light, the photogenerated electron-hole pairs have higher redox ability, which allows them to react with water molecules and dissolved oxygen to generate a variety of active oxidizing species to efficiently degrade pollutants. x Ti y The photogenerated electrons of O5 are transferred to In2S3 across the heterojunction interface, reducing the recombination of electron-hole pairs and greatly enhancing the carrier interface separation efficiency. The emergence of covalent bonds ensures the structural stability of the composite material, while also solving the solubility problem of perovskite materials in aqueous phase to a certain extent and improving the reusability of the material.

[0026] The beneficial effects of the present invention are:

[0027] The present invention constructs a heterojunction to bind Mg x Ti y O5 and In2S3 are combined to construct a titanium-based perovskite oxide heterojunction catalytic material with stronger interface carrier separation ability, light absorption range covering the entire visible spectrum, and higher catalytic activity - Mg x Ti y O5 / In2S3.Mg x Ti yO5 materials are prone to produce other byproducts during the preparation process. They also have a wide band gap and low charge separation efficiency. The traditional two-dimensional material g-C3N4 cannot achieve effective full visible spectrum absorption when combined with it. Further modification is still required, which makes the synthesis steps complicated. In2S3 avoids such problems and has better optical absorption than traditional g-C3N4 and CdSe. x Ti y O5 and In2S3 composite successfully realize Mg x Ti y The photogenerated electron-hole pairs of O5 / In2S3 composite photocatalytic nanomaterials are separated at the heterojunction interface, avoiding the electron-hole recombination problem in the band gap of a single nanomaterial. The matching energy level position arrangement enables the two to accelerate the migration and separation of photogenerated charges. The construction of the heterojunction more effectively enhances the charge separation and electron transfer at the heterojunction interface, greatly improving the photocatalytic activity. x Ti y The O5 / In2S3 photocatalytic system achieves effective pollutant degradation and has the characteristics of simple synthesis method, good stability and reusability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope image of MgTi2O5 / In2S3 prepared in Example 1 of the present invention;

[0029] Figure 2 The ultraviolet diffuse reflectance spectra of MgTi2O5 / In2S3, MgTi2O5, and In2S3 prepared in Example 1 and Comparative Examples 1 and 2 of the present invention are shown;

[0030] Figure 3 Fourier transform infrared spectra of MgTi2O5 / In2S3, MgTi2O5, and In2S3 prepared in Example 1 and Comparative Examples 1 and 2 of the present invention;

[0031] Figure 4 This is a performance comparison chart of MgTi2O5 / In2S3, MgTi2O5, and In2S3 prepared in Example 1 of the present invention and Comparative Examples 1 and 2 for photocatalytic degradation of bisphenol A;

[0032] Figure 5 This is a degradation diagram of the reusability experiment of photocatalytic degradation of bisphenol A by MgTi2O5 / In2S3 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0034] Embodiment 1,

[0035] A method for preparing a titanium-based perovskite oxide heterojunction catalytic material, characterized by comprising the following steps:

[0036] A. Dissolve 3.84 g of magnesium nitrate hexahydrate and 12 g of urea in 30 mL of deionized water, then disperse 5.724 g of titanium isopropoxide in 40 mL of ethylene glycol solution, and mix the two solutions in a round-bottom flask; then stir the solution mixture at 90 ° C until the solvent is completely evaporated; finally, place the obtained white powder in a muffle furnace and heat it to 600 ° C at 2 ° C / min for 2 h to remove impurity ions to obtain nanoparticles of MgTi2O5;

[0037] B. Disperse 0.25mmol MgTi2O5, 1.0mmol InCl3·4H2O, 2.0mmol thioacetamide and 1.7mmol urea in 50mL 50% (volume fraction) ethanol aqueous solution. After continuous stirring at 600r / min for 60min, transfer the solution to a 100mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 180°C for 12h. After the solution is naturally cooled to room temperature, centrifuge, wash with deionized water and ethanol three times each, and then dry at 60°C to constant weight to obtain the yellow catalytic material MgTi2O5 / In2S3.

[0038] Figure 1 This is a scanning electron microscope image of MgTi2O5 / In2S3 prepared in Example 1. Figure 1 As shown, In2S3 nanoparticles are distributed on MgTi2O5 nanorods, and this in situ grown close contact provides a potential channel for rapid photoinduced charge transfer across the heterointerface.

[0039] Comparative Example 1

[0040] Only the catalyst MgTi2O5 was prepared:

[0041] 3.072 g of magnesium nitrate hexahydrate and 12 g of urea were dissolved in 30 mL of deionized water, and then 5.152 g of titanium isopropoxide was dispersed in 40 mL of ethylene glycol solution. The two solutions were placed in a round-bottom flask and mixed; the solution mixture was then stirred continuously at 100 ° C until the solvent was completely evaporated; finally, the obtained white powder was placed in a muffle furnace and heated to 500 ° C at 2 ° C / min for 4 hours to remove impurity ions, thereby obtaining nanoparticles of MgTi2O5;

[0042] Comparative Example 2

[0043] Prepare only the catalyst In2S3:

[0044] 1.0 mmol InCl3·4H2O, 2.0 mmol thioacetamide and 1.7 mmol urea were dispersed in 50 mL 50% (volume fraction) ethanol aqueous solution. After continuous stirring at 600 r / min for 60 min, the solution was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 180 °C for 12 h. After the solution was naturally cooled to room temperature, it was centrifuged, washed with deionized water and ethanol three times each, and then dried at 60 °C to constant weight to obtain a dark yellow material In2S3.

[0045] Embodiment 2,

[0046] A method for preparing a titanium-based perovskite oxide heterojunction catalytic material, characterized by comprising the following steps:

[0047] A. Dissolve 3.84 g of magnesium nitrate hexahydrate and 12 g of urea in 30 mL of deionized water, then disperse 5.801 g of titanium isopropoxide in 40 mL of ethylene glycol solution, and mix the two solutions in a round-bottom flask; then stir the solution mixture at 80 °C until the solvent evaporates completely; finally, place the obtained white powder in a muffle furnace and heat it to 600 °C at 5 °C / min for 2 h to remove impurity ions, thereby obtaining nanoparticles of Mg 1.2 Ti 1.8 O5;

[0048] B. 0.5 mmol Mg 1.2 Ti 1.8 O5, 1.0 mmol InCl3·4H2O, 2.0 mmol thioacetamide and 1.7 mmol urea were dispersed in 50 mL 50% (volume fraction) ethanol aqueous solution. After continuous stirring at 600 r / min for 60 min, the solution was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 200 °C for 10 h. After the solution was naturally cooled to room temperature, it was centrifuged, washed with deionized water and ethanol three times each, and then dried at 60 °C to constant weight to obtain the yellow catalytic material Mg 1.2 Ti 1.8 O5 / In2S3.

[0049] Embodiment 3,

[0050] A method for preparing a titanium-based perovskite oxide heterojunction catalytic material, characterized by comprising the following steps:

[0051] A. 3.533 g of magnesium nitrate hexahydrate and 12 g of urea were dissolved in 30 mL of deionized water, and then 5.266 g of titanium isopropoxide was dispersed in 40 mL of ethylene glycol solution. The two solutions were placed in a round-bottom flask and mixed; the solution mixture was then stirred at 90 ° C until the solvent was completely evaporated; finally, the obtained white powder was placed in a muffle furnace and heated to 500 ° C at 10 ° C / min for 4 h to remove impurity ions, and the nanoparticles of Mg 1.2 Ti 1.8 O5;

[0052] B. 1.0mmol Mg 1.2 Ti 1.8 O5, 1.0mmol InCl3·4H2O, 2.0mmol thioacetamide and 1.7mmol urea were dispersed in 50mL 50% (volume fraction) ethanol aqueous solution. After continuous stirring at 600r / min for 60min, the solution was transferred to a 100mL polytetrafluoroethylene-lined hydrothermal reactor for hydrothermal reaction at 160℃ for 14h. After the solution was naturally cooled to room temperature, it was centrifuged, washed with deionized water and ethanol for 3 times each, and then dried at 60℃ to constant weight to obtain the yellow catalytic material Mg 1.2 Ti 1.8 O5 / In2S3.

[0053] 1. Evaluation of photocatalytic degradation performance

[0054] The photocatalytic degradation performance of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 was evaluated as follows:

[0055] The photodegradation process was carried out in a 250 mL custom-made double-walled quartz beaker with a cooling water circulation system to keep the reaction temperature constant. A 300 W xenon lamp (350 nm < λ < 800 nm) was used as the light source with an average light intensity of 200 mW / cm 2 . Before the reaction started, 50 mg of the photocatalyst was dispersed in a bisphenol A solution (10 mg / L), and the pH value was controlled at about 7 with 0.1 M hydrochloric acid or sodium hydroxide solution. The suspension was stirred continuously during the entire reaction. A dark adsorption experiment was performed 30 minutes before illumination to achieve the adsorption-desorption equilibrium between bisphenol A and the photocatalyst. Then, 1 mM PMS was added. During the photodegradation process, 1 mL of the reaction solution was taken out at regular intervals and then passed through a 0.22 μm filter to prepare for ultra-high performance liquid chromatography analysis. The mobile phase was acetonitrile and ultrapure water in a volume ratio of 50:50, and the detection wavelength was 278 nm. The relative concentration (C / C0) was used to calculate the degradation efficiency.

[0056] Figure 2The UV diffuse reflectance spectra of MgTi2O5 / In2S3, MgTi2O5, and In2S3 prepared in Example 1 and Comparative Examples 1 and 2 are shown in FIG. Figure 2 As shown, In2S3 exhibits strong spectral absorption in the entire ultraviolet and visible light regions. Compared with the limited light absorption cutoff edge of traditional two-dimensional materials such as g-C3N4, its spectral absorption is significantly enhanced, with a cutoff edge of about 650nm and a slightly weaker absorption tail peak. The light absorption cutoff edge of single MgTi2O5 is about 350nm, indicating that its absorption of visible light is weak. For the composite material MgTi2O5 / In2S3, it can be seen that the loading of In2S3 effectively retains the absorption tail peak intensity of the material, and significantly enhances the light absorption in the range of 400-650nm, effectively improving the visible light capture efficiency of the composite material.

[0057] Figure 3 The Fourier transform infrared spectra of MgTi2O5 / In2S3, MgTi2O5, and In2S3 prepared in Example 1 and Comparative Examples 1 and 2 are shown in Figure 1. For MgTi2O5, 500 cm -1 The absorption peak near 600cm belongs to the stretching vibration of Mg-O bond. -1 - 750cm -1 The absorption peak at 3400 cm is attributed to the Ti-O bond. -1 The absorption peak at 646cm belongs to the OH vibration of water molecules adsorbed on the surface of the material. -1 The absorption band near 1494 cm-1 corresponds to the vibration of In-S bond. -1 The weak band near 3110 cm -1 -3660cm -1 The broad absorption peak in the region corresponds to the OH group of the adsorbed water molecules. At the same time, the main typical absorption peaks of the original MgTi2O5 and In2S3 are present in the MgTi2O5 / In2S3 sample, which further indicates the successful synthesis of the MgTi2O5 / In2S3 composite catalyst. In addition, at 877cm -1 A new peak was found at , indicating that SO bonds were formed at the MgTi2O5 / In2S3 heterointerface and strong chemical interactions occurred, which promoted the rapid migration of electrons. The emergence of covalent bonds ensured the structural stability of the composite material.

[0058] Figure 4 The performance comparison chart of MgTi2O5 / In2S3, MgTi2O5, and In2S3 prepared in Example 1 and Comparative Examples 1 and 2 for photocatalytic degradation of bisphenol A is shown in FIG. Figure 4As shown, the experimental results show that under the conditions of catalyst dosage of 0.5g / L, initial bisphenol A concentration of 5mg / L and initial temperature of room temperature, the degradation efficiency of bisphenol A by single MgTi2O5 / PMS and In2S3 / PMS systems were 43.87% and 69.88% respectively within 15min, while the removal rate of bisphenol A by MgTi2O5 / In2S3 / PMS system reached 98.05%, which means that the loading of In2S3 enables the composite material to utilize more visible light. At the same time, the construction of Z-type heterojunction effectively improves the interfacial charge transfer of photogenerated carriers and inhibits the in-situ recombination of photogenerated electron-hole pairs in two single photocatalysts.

[0059] 2. Continuous degradation experiment

[0060] After the first degradation reaction of the catalyst prepared in Example 1 was completed, the post-reaction solution was centrifuged and washed, and the recovered catalyst was dried in a freeze dryer for 48 h, and then put into the reactor again for the next degradation experiment. Except for the materials, the other degradation reaction conditions were consistent with the first photocatalytic degradation performance evaluation experiment setting procedure; after the second reaction was completed, the above steps were repeated to carry out three degradation experiments.

[0061] Figure 5 This is a degradation diagram of the reusability experiment of photocatalytic degradation of bisphenol A by MgTi2O5 / In2S3 prepared in Example 1. Figure 5 As shown, the degradation efficiency of bisphenol A was above 95% in three consecutive degradation experiments, indicating that the photocatalytic activity of MgTi2O5 / In2S3 photocatalytic nanomaterials remained good after three cycles. This shows that distributing In2S3 nanoparticles on MgTi2O5 nanorods is beneficial to solving the problems of insufficient visible light absorption of the material and instability of perovskite materials in the aqueous phase.

[0062] Organic pollutants degraded by MgTi2O5 / In2S3 include but are not limited to bisphenol A, atrazine, carbamazepine, tetracycline, rhodamine b, etc. Preferably, the MgTi2O5 / In2S3 of the present invention has an exceptionally excellent degradation effect on bisphenol A under photocatalytic conditions. On the one hand, the photocatalytic material MgTi2O5 / In2S3 is photoexcited to generate photogenerated electrons and photogenerated holes under the irradiation of a xenon lamp. The matching energy level position enables the photogenerated electrons of the In2S3 conduction band to be transferred across the heterojunction interface to the MgTi2O5 valence band. This Z-type charge transfer mechanism not only promotes carrier separation, but also retains strong redox ability. On the other hand, the built-in electric field generated between the two under electrostatic interaction further induces electrons to migrate from In2S3 to MgTi2O5, and the electron cross-interface transfer will effectively inhibit the recombination of electron-hole pairs, thereby significantly improving the charge separation efficiency. Finally, the pollutants are oxidized by surface active oxygen or hydroxyl groups and holes, and finally generate water and carbon dioxide.

Claims

1. A method for preparing a titanium-based perovskite oxide heterojunction catalytic material, characterized in that The following steps are involved: A. Dissolve magnesium nitrate hexahydrate and urea in deionized water, then disperse titanium isopropoxide in ethylene glycol solution, the mass ratio of magnesium nitrate hexahydrate, urea and titanium isopropoxide is 3-4:12:5-6, mix the above two solutions; then continue to stir the solution mixture at 80-100°C until the solvent is completely evaporated; finally, calcine the obtained powder to remove impurity ions to obtain nanoparticles of Mg x Ti y O5; B. Mg x Ti y O5, InCl3·4H2O, thioacetamide and urea were dispersed in an ethanol aqueous solution. After continuous stirring, the solution was subjected to a hydrothermal reaction. After the solution was naturally cooled to room temperature, it was centrifuged, washed, and then dried to a constant weight to obtain a catalytic material Mg x Ti y O5 / In2S3.

2. The method for preparing a titanium-based perovskite oxide heterojunction catalytic material according to claim 1, characterized in that: In step A, the temperature is raised to 500-600° C. at a rate of 2-10° C. / min and the calcination is carried out for 2-4 h.

3. The method for preparing a titanium-based perovskite oxide heterojunction catalytic material according to claim 1, characterized in that: In step B, Mg x Ti y The molar ratio of O5, InCl3·4H2O, thioacetamide and urea is 0.25-1.0:1:2:1.

7.

4. The method for preparing a titanium-based perovskite oxide heterojunction catalytic material according to claim 1, characterized in that: In step B, the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 10-14 h.

5. A titanium-based perovskite oxide heterojunction catalytic material, characterized in that: The material is prepared by the method for preparing the titanium-based perovskite oxide heterojunction catalytic material according to any one of claims 1 to 4.

6. Use of the titanium-based perovskite oxide heterojunction catalytic material according to claim 5 in photocatalytic degradation of pollutants.

7. An application of the titanium-based perovskite oxide heterojunction catalytic material according to claim 6 in photocatalytic degradation of pollutants, characterized in that: The contaminants include bisphenol A.

Citation Information

Patent Citations

  • Preparation method of MgTi2O5 nano catalyst

    CN104826620A

  • Method for catalytically synthesizing H2O2

    CN113086950A